DIFFERENCES IN THE ACHIEVEMENT OF ENGLISH LANGUAGE ESSENCE BETWEEN INTROVERT AND EXTROVERT PERSONALITY TYPES - Balqis Husain; Saifudin S. Adam (Peneliti.net, 2018)
This research aims to know the differences achievement in English essay writing between introvert and extrovert personality types toward high school students of Morotai. Design of this research used quantitative and focused to the comparative method. Population of this research was high school students in the regency of Morotai Island that separated in the 5 sub-district. Sampling technique of this research used Simple Random sampling by using Krechie Morgan’s Table. Thus, sample of this research was 174 students with total of population were 323 students. Instrument that was used in this research were 2 instruments, they are 1) questionnaire; to measure the students personality types. 2) Writing test; to measure the students’ ability in writing. Analyze the data in this research used Independent t-test. Based on the EPI scale, the result shown that 40 students were introvert dan 134 students were extrovert. Based on the Independent T-test result, significant value α =0.077> α = 0.05, the result proved that there were no significant differences in English essay writing achievement between introvert and extrovert personality.